2002
DOI: 10.1046/j.1365-2559.2002.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear to cytoplasmic compartment shift of the p33ING1b tumour suppressor protein is associated with malignancy in melanocytic lesions

Abstract: Cytoplasmic immunostaining for p33ING1b using MAb GN2 is strongly associated with 'activated' melanocytic lesions; therefore it is possible that this MAb could be of value in diagnostic practice. Furthermore, the reduction in p33ING1b expression and perhaps translocation from the nucleus to the cytoplasm may play a central role in the development and progression of melanomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 30 publications
(45 reference statements)
4
43
0
Order By: Relevance
“…In this study, we found that rapid ING3 degradation has an important role in the loss of ING3 expression in advanced melanomas, thereby providing another explanation of aberrant ING3 expression in melanomas in addition to our previous finding that subcellular relocalization of ING3 causes its deregulation in both primary and metastatic melanomas (Wang et al, 2007). Meanwhile, ING1b has been shown to be shifted from the nucleus to the cytoplasm in melanocytic lesions (Nouman et al, 2002), which may be mediated by 14-3-3 proteins (Gong et al, 2006). Both nuclear ING2 and overall ING4 expressions are also downregulated in melanomas, although only the reduced ING4 expression was significantly associated with melanoma progression (Lu et al, 2006;Li et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we found that rapid ING3 degradation has an important role in the loss of ING3 expression in advanced melanomas, thereby providing another explanation of aberrant ING3 expression in melanomas in addition to our previous finding that subcellular relocalization of ING3 causes its deregulation in both primary and metastatic melanomas (Wang et al, 2007). Meanwhile, ING1b has been shown to be shifted from the nucleus to the cytoplasm in melanocytic lesions (Nouman et al, 2002), which may be mediated by 14-3-3 proteins (Gong et al, 2006). Both nuclear ING2 and overall ING4 expressions are also downregulated in melanomas, although only the reduced ING4 expression was significantly associated with melanoma progression (Lu et al, 2006;Li et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…ING1b exhibited proliferation-inhibitory, apoptosis-promoting, and cell cycle-arrest effects in both benign and malignant cells [20][21][22][23][24][25][26][27][28][29]. These data, along with the results of reduced expression of p33 ING1b in gastric adenocarcinoma tissues, provide substantial evidence that p33…”
Section: P33mentioning
confidence: 76%
“…ING1b expression was down-regulated in the gastric adenocarcinoma cell lines SGC-7901, MKN28, and MKN45 compared with the normal by nucleus-to-cytoplasm translocation in cancer cells [11,22]. Based on these results, it can be concluded that decreased expression of p33 ING1b is a common phenomenon in gastric adenocarcinoma, and this alteration might contribute to the development of gastric adenocarcinoma.…”
Section: P33mentioning
confidence: 77%
“…Additionally, a loss of nuclear localization and an increase of cytoplasmic localization of ING1 has been observed in melanoma, ductal breast and papillary thyroid carcinomas and lymphoblastic leukaemia. [37][38][39] To understand the molecular basis of histone recognition by the ING1 PHD finger and to further our knowledge of tumorigenic mechanisms, we determined a 2.1 Å resolution crystal structure of the PHD finger of human ING1 in complex with a H3K4me3 peptide and elucidated the role of cancer specific mutations in the histone binding and function of ING1.…”
Section: Introductionmentioning
confidence: 99%